Comparative estimations of betalains and sugars in fruits of five species of Selenicereus (Cactaceae): Betalains and sugars in pitahayas - Pérez-Orozco, Arith F.; Sosa, Victoria (Instituto de Ecología, A.C., 2022)
Background and Aims: Betalains are water pigments reported for most species in the order Caryophyllales, to which the family Cactaceae belongs, with benefits as antioxidants in nutrition and human health. The objective of this paper is to determine the quantity of the betalains (betaxanthins and betacyanins) and sugars present in five taxa of Selenicereus, from the Hylocereus clade, commonly utilized for their edible fruit, including S. ocamponis which is an underutilized species, and scarcely cultivated in Mexico. Methods: Fruits from wild and cultivated plants were collected in Puebla, Veracruz and Yucatán (Mexico) and Valle del Cauca (Colombia) between April and June 2019, and their betalain and sugar content were estimated from frozen fruit. The method proposed by the Association of Official Analytical Chemists was followed to estimate the sugar content. A spectrophotometric method was utilized for estimation of betalains. Key results: The highest total betalain content was found in species with fruits of purple pulp and pericarp such as S. ocamponis (5.30 and 4.03 mg/100 g of fresh weight, respectively). Glucose and fructose content was considerable in some samples: S. undatus with 5.99 and 2.87 mg/100 g and S. ocamponis with 5.30 and 4.03 mg/100 g respectively. Conclusions: This study identified large variation in total betalain content in the pericarps of wild and cultivated fruits in S. undatus (2.47-37.11 mg/100 g of fresh weight), which might be related to their management and selection. Estimated total betalain content of wild plants of this species was higher than in some cultivated plants. These results suggest that wild S. undatus plants might represent a good source for breeding programs. The cultivation of species with purple pulp and pericarp should be promoted, so they can be utilized as colorants in food industry.